Sistem Pengendalian Kecepatan Pada Quadcopter Dengan Menggunakan Metode Linear Quadratic Regulator (LQR) - Mesra Diana Tamsar; Gembong Edhi Setyawan; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Unmanned Aerial Vehicle (UAV) is an unmanned aircraft that is widely used by the community. One type of UAV is a quadcopter. Quadcopter is often used in various fields namely military, industry and others. Quadcopter has four rotor with different speed for each rotor. One of the problems on the quadcopter is controlling speed. The speed of the quadcopter at the time of movement is not the same as the speed assigned by the user. This can lead to the occurrence of friendship and the presence of accidents on quadcopter. Use of Linear Quadratic Regulator (LQR) to stabilize speed. The first step done in this research is to calculate LQR that is by determining matrix A, B, C, D which will be implemented in quadcopter. The next stage is to input the distance on to be taken by the quadcopter. This test is done by testing the stability of the speed for each distance in the input by the user, as well as the accuracy of the distance traveled quadcopter. The distance used by the user is 1m, 1.5m, 2m, 2.5m, and 3m. The results of the tests that have been done to obtain the results with the accuracy of the distance traveled is in accordance with the distance used by the user and for speed also remain stable for every distance traveled. The average time required by the quadcopter to reach any distance in sequence is 1.2 seconds, 2.43 seconds, 2.07 seconds, 3.35 seconds and 4.07 seconds.